The Importance of The Hard and Soft Skills of Economic Graduates in the Opinion of Academic Staff and Managers - Hubert OBORA; Małgorzata TYRAŃSKA; Maciej WALCZAK; Angelika WODECKA-HYJEK (Communications of International Proceedings, 2021)
It can be argued that certain changes that have taken place over the past few decades, such as market globalization, the internationalization of business relations, and the impact of COVID-19 pandemic restrictions, will trigger a necessary metamorphosis in the skills that employees must possess if they wish to prove themselves on a labour market currently undergoing transformation. A review of the current research on the teaching of skills and competences desired by managers on the labour market clearly highlights the complementarity of hard and soft skills. The aim of the article is to identify differences in how the importance of the hard and soft skills of economics graduates are assessed by academic staff and representatives from the world of work. The method used for the present analysis was a structured interview with experts, which itself was based on a survey questionnaire. A total of 43 experts, divided into two groups, participated in the study, which was conducted in November-December 2020. The respondents assessed the importance of the skills included in the proposed competency model for economics graduates based on the five-point Likert scale. Research indicates that soft skills are of greater importance than hard skills. What appears particularly noteworthy is the fact that this view is held above all by recruiters and managers. The article has added value in that it identifies the growing significance of soft skills for economics graduates, which in turn suggests a need to revise and optimize curricula.
Keywords: Competency Model; Hard Skills; Soft Skills; Higher Education.